2004
DOI: 10.1118/1.1791352
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the reference air kerma rate for brachytherapy sources and the related uncertainty

Abstract: Different methods exist to determine the air kerma calibration factor of an ionization chamber for the spectrum of a 192Ir high-dose-rate (HDR) or pulsed-dose-rate (PDR) source. An analysis of two methods to obtain such a calibration factor was performed: (i) the method recommended by [Goetsch et al., Med. Phys. 18, 462-467 (1991)] and (ii) the method employed by the Dutch national standards institute NMi [Petersen et al., Report S-EI-94.01 (NMi, Delft, The Netherlands, 1994)]. This analysis showed a systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 13 publications
0
22
1
Order By: Relevance
“…In recent years, publications by Mainegra-Hing and Rogers 4 and van Dijk et al 5 have provided alternatives to the interpolation methodology used in the original standard. The consensus from those publications was that the interpolation should be based on parameters that are proportional to ion chamber response.…”
Section: Iib Interpolation Methods For N Kmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, publications by Mainegra-Hing and Rogers 4 and van Dijk et al 5 have provided alternatives to the interpolation methodology used in the original standard. The consensus from those publications was that the interpolation should be based on parameters that are proportional to ion chamber response.…”
Section: Iib Interpolation Methods For N Kmentioning
confidence: 99%
“…During recent years, the methods on which the original stand-ard was based have been critiqued, and improved methods have been suggested by several researchers. The original standard used a linear interpolation between A wall weighted air-kerma calibration coefficients, but the works of Mainegra-Hing and Rogers 4 and van Dijk et al 5 have shown that it would be more appropriate to use an interpolation based on the inverse of the air-kerma calibration coefficients and without the inclusion of A wall weighting. In addition, van Dijk et al suggested an interpolation using the spectral lines of 192 Ir.…”
Section: Introductionmentioning
confidence: 99%
“…Some issues related to this method have been discussed and improvements to this method have been proposed. [9][10][11][12] On the other hand, to date, the determination of absorbed dose in water or plastic phantoms for HDR 192 Ir brachytherapy sources has been reported for direct inphantom measurements using detectors such as Fricke dosimeters, 13,14 thermoluminescent dosimeters, 3,4 radiophotoluminescent glass dosimeters, 15 ionization chamber dosimeters, [16][17][18][19][20][21][22] diode dosimeters, 3 metal-oxide semiconductor field-effect transistor dosimeters, 23 and Gafchromic film dosimeters. 21,22,24,25 Absorbed dose standards for HDR 192 Ir sources based on water and graphite calorimeters have recently been developed in the framework of the European Metrology Research Programme (EMRP) from 2008 to 2011.…”
Section: Introductionmentioning
confidence: 99%
“…To replace the interpolation techniques between air-kerma calibration coefficients of an ionization chamber for 192 Ir [5, 6], the Institute of Nuclear Energy Research (INER, Taiwan) has recently developed a spherical graphite-walled cavity ionization chamber as the primary standard for direct measurement of HDR 192 Ir brachytherapy source strength to provide a traceable source calibration. Our primary standard is derived from measurements using the graphite-walled chamber, based on the Bragg-Gray theory.…”
Section: Introductionmentioning
confidence: 99%